RESEARCH ON THE AGRARIAN STRUCTURE IN POLAND IN SPATIAL GRASP - Kukuła, Karol (Acta Scientiarum Polonorum. Oeconomia, 2007)
The paper presents the analisys of four agrarian structures at the level of voivodships in Poland. As a result of the application of the relevant taxonomic procedure groups of voivodships of similar agrarian structures have been obtained. Each group has been shortly characterised.